2011
DOI: 10.1021/es201239f
|View full text |Cite
|
Sign up to set email alerts
|

A Microarray Biosensor for Multiplexed Detection of Microbes Using Grating-Coupled Surface Plasmon Resonance Imaging

Abstract: Grating-coupled surface plasmon resonance imaging (GCSPRI) utilizes an optical diffraction grating embossed on a gold-coated sensor chip to couple collimated incident light into surface plasmons. The angle at which this coupling occurs is sensitive to the capture of analyte at the chip surface. This approach permits the use of disposable biosensor chips that can be mass-produced at low cost and spotted in microarray format to greatly increase multiplexing capabilities. The current GCSPRI instrument has the cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 81 publications
0
37
0
Order By: Relevance
“…In a study which a gold-plated microchip biosensor was designed for the detection of L. monocytogenes and different pathogens by diffraction-network coupled surface plasmon resonance imaging, known as combining the parallel light with surface plasmons, two different monoclonal anti-Listeria antibodies and one rabbit polyclonal anti-Listeria antibody and the negative control antibodies were immobilized on microchips at equivalent concentrations and analyzed with a sample containing L. monocytogenes heat-killed at a concentration of 1.65x10 9 cfu/ml in PBS with 0.5% Tween 20. It has been found LZF monoclonal antibody caused deviation with a much larger resonance angle than LZH1 polyclonal antibody and reported that the slight differences in the affinity for L. monocytogenes of the antibodies may be due to the procedure used to kill the pathogen (Marusov et al 2012). Together this study, the single-use chips were opened and compact microarray sensoric chips were equipped with antibodies or other specific recognition molecules for multiplex analyte detection.…”
Section: Surface Plasmon Resonance Based Biosensorsmentioning
confidence: 93%
“…In a study which a gold-plated microchip biosensor was designed for the detection of L. monocytogenes and different pathogens by diffraction-network coupled surface plasmon resonance imaging, known as combining the parallel light with surface plasmons, two different monoclonal anti-Listeria antibodies and one rabbit polyclonal anti-Listeria antibody and the negative control antibodies were immobilized on microchips at equivalent concentrations and analyzed with a sample containing L. monocytogenes heat-killed at a concentration of 1.65x10 9 cfu/ml in PBS with 0.5% Tween 20. It has been found LZF monoclonal antibody caused deviation with a much larger resonance angle than LZH1 polyclonal antibody and reported that the slight differences in the affinity for L. monocytogenes of the antibodies may be due to the procedure used to kill the pathogen (Marusov et al 2012). Together this study, the single-use chips were opened and compact microarray sensoric chips were equipped with antibodies or other specific recognition molecules for multiplex analyte detection.…”
Section: Surface Plasmon Resonance Based Biosensorsmentioning
confidence: 93%
“…GCSPRI sensor chips were prepared and GCSPRI assays were performed as previously described [35]. Gold-coated GCSPR sensor chips were obtained from Ciencia, Inc. (East Hartford, CT, USA).…”
Section: Methodsmentioning
confidence: 99%
“…This was followed by plating of the cells on an oxford agar (incubated overnight), after which colonies were differentiated with fluorescently labelled endolysins and their subsequent detection by fluorescence microscopy in less than 15 min. Recently, Marusov et al (2012) utilized gratingcoupled SPR imaging to detect the microbes. In this method a gold-coated sensor chip has been used to couple collimated incident light with surface plasmons that permits the use of disposable biosensor chips.…”
Section: Surface Plasmon Resonance (Spr)-based Biosensorsmentioning
confidence: 99%